594 Urinary incontinence and intention to leave current job. (24th April 2018) - Pierce, Heather; Perry, Lin; Gallagher, Robyn; Chiarelli, Pauline
Abstract : Introduction: Urinary incontinence (UI) is a condition prevalent in women, with negative impact on pyschosocial health and quality of life. The aim of this study was to examine the relationship between urinary incontinence and work. Methods: An electronic survey was distributed between May 2014 and February 2015 to members of the New South Wales Nurses and Midwives Association in Australia. Urinary incontinence prevalence and severity was investigated using the International Consultation on Incontinence Questionnaire Urinary Incontinence – Short Form. Demographic, general and female reproductive health data known to influence the reporting of UI were collected. Investigated work characteristics included: work role, contract, shift, job satisfaction and plans to leave current job. Data analyses included female respondants and excluded those with a curent pregnancy or urinary tract infection 'sometimes or often' in the last 12 months. Results: The final sample size was 2, 907, of mean age 47.35 years (19–74±11.58); mean Body Mass Index 28.09 kg/m2 (15–57±6.41); 69.9% were parous. The prevalence of any UI in the past 4 weeks was 32.0% (95% CI: 30% to 34%; n=930). Slight severity UI was present in 55.2%, moderate UI in 40.5% and severe UI in 4.4%. Those with severe UI were more dissatisfied with their work (p=0.001) and more likely to intend to leave their current position in the next 12 months than those with slight or moderate symptoms (OR: 2.26; 95% CI: 1.02 to 5.01) after accounting for age, Body Mass Index, parity, anxiety, depression, work contract, shift and job satisfaction. Conclusion: UI is a health concern for women in the workforce, associated with reduced job satisfaction and an intention to leave current job. The findings of this study flag the need to raise the awareness of this common condition in the workplace as UI is a treatable and preventable condition.